Odpowiedzi

Najlepsza Odpowiedź!
2010-03-13T19:22:55+01:00
4(2x+3)-2(4y-1)=30
(5x+1):3-(y-3):4=3

8x+12 -8y+2 = 30
5/3x +1/3 -y/4+3/4 =3/ *12

8x-8y = 16
20x+4 -3y+9 = =36

8x-8y=16/*(-3_
20x-3y=23/*8

-24x+24y=-48
160x-24y = 184

skracam 24 i 24

136x = 136 /:136
x = 1

Podstawiam za X

8x-8y=16
8*1 -8y= 16

-8y = 8 /:(-8)
y = -1

więc
x=1
y= -1


2 5 2
2010-03-13T19:28:05+01:00
{ 4(2x+3)-2(4y-1) = 30
{ (5x+1)/3-(y-3)/4 = 3

{ 8x+12-8y+2 = 30
{ 5/3x+1/3-y/4+3/4 = 3/*12

{ 8x-8y = 16
{ 20x+4 -3y+9 = 36

{ 8x-8y = 16/*(-3)
{ 20x-3y = 23/*8

{ -24x+24y = -48
{ 160x-24y = 184

{ 136x = 136 /:136
{ x = 1

{ 8x-8y =16
{ 8*1-8y = 16

{ -8y = 8 /:(-8)
{ y = -1

{ x = 1
{ y = -1
Wydaje mi się, że dobrze jest ;)
1 4 1